Новые и малоизвестные виды рода эндотения — Endothenia Stрh. (Lepidoptera, Tortricidae) фауны СССР - Фалькович, М.И. (Вестник зоологии, 1970)
В статье содержится описание трех новых видов листоверток рода Endothenia S t р h. Е. furvida Flkv. , sp. п. распространена на Дальнем
Востоке и в Южной Сибири; Е. ingrata Flkv. , sp. п. и Е. remigera Flkv. , sp. п. найтены лишь в Южном Приморье. Дальневосточная Е. atrata
С а г., считавшаяся формой Е. lapideana H.-S., выделяется" в самостоятельный вид. На основе исследования типов <Grapholitha» desertana
S t g г. сводится в синоним Endothenia gentianaeana Н b., а Е. adustana К г о g. — в синоним Е. hebesana W к г. The article deals with the descriptions of three new species of the genus Endothenia St ph.: E jurpida Fl к v. sp. n., distributed in the Far East and in South Siberia, E. ingrata FI к v. sp. n. and E. remigera F l к v. sp. n., which are found only in the south of the Far East (Primorye territory). The Far-Eastern E. atrata Car. regarded by Caradja as a form of E. lapideana H.-S. is considered as a valid species. After examining the types the author considers «Grapholitha-» desertana S t g r. as a synonym to Endothenia gentianaeana H b., and E. adustana К г о g. as a synonym to E. hebesana W к r.